1988
DOI: 10.1111/j.1471-4159.1988.tb13262.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amphetamine on Protein Synthesis and Energy Metabolism in Mouse Brain: Role of Drug‐Induced Hyperthermia

Abstract: Changes in brain protein synthesis activity, and in brain levels of glucose, glycogen, and several high-energy phosphate metabolites, were evaluated under conditions of amphetamine-induced hyperthermia in mice. Protein synthesis showed a striking dependence on rectal temperature (TR), falling abruptly at TR above 40 degrees C. A similar result was obtained following direct heating of the animals. Protein synthesis activity in liver showed the same temperature dependence observed for brain. Increased synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
14
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 70 publications
(49 reference statements)
5
14
0
Order By: Relevance
“…In further support of this view is the present finding that maintenance of rats at a modestly cool ambient temperature (i.e., 17°C) prevented not only MDMA-induced glycogenolysis but also MDMA-induced hyperthermia. This finding is in agreement with the work of Nowak (1988), who reported that amphetamine-induced hyperthermia and glycogenolysis were less at 17 than at 27°C. Also consistent with a role of hyperthermia in the MDMA-induced alteration in energy regulation is the finding that the administration of MDMA via reverse dialysis into the striatum did not alter the extracellular concentration of glucose, whereas a significant increase was observed following the systemic administration of MDMA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In further support of this view is the present finding that maintenance of rats at a modestly cool ambient temperature (i.e., 17°C) prevented not only MDMA-induced glycogenolysis but also MDMA-induced hyperthermia. This finding is in agreement with the work of Nowak (1988), who reported that amphetamine-induced hyperthermia and glycogenolysis were less at 17 than at 27°C. Also consistent with a role of hyperthermia in the MDMA-induced alteration in energy regulation is the finding that the administration of MDMA via reverse dialysis into the striatum did not alter the extracellular concentration of glucose, whereas a significant increase was observed following the systemic administration of MDMA.…”
Section: Discussionsupporting
confidence: 93%
“…The induction of glycogen breakdown elicited by MDMA is consistent with the effects of other amphetamine analogs on brain glycogen content. Both PCA and d-amphetamine have been reported to reduce brain glycogen content (Nahorski and Rogers, 1975;Nowak, 1988;Heuther et al, 1997). Poblete and Azmitia (1995) have reported that under in vitro conditions MDMA increases the activity of glycogen phosphorylase, the enzyme responsible for the breakdown of glycogen.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects on glycogen content have also been noted in studies with d-amphetamine and other amphetamine analogs (Nahorski and Rogers, 1973;Nowak, 1988). Although these prior studies implicate an effect of stimulants on energy production in the brain, recent work has also shown a role for skeletal muscle in MDMA-mediated hyperthermia .…”
supporting
confidence: 63%
“…In mammalian cells, HSP expression is induced in vivo in mammalian brain and other organs during hyperthermia (51), ischemia (52), and exposure to neurotoxin (53). Abnormal expression of HSPs has been described in a variety of pathophysiological states, which include fever, inflammation, oxidant injury, viral infection, and cancer (54), and a cytoprotective role of HSPs and HSP70 in particular has been shown in several pathological conditions, including ischemia (55) and virus infection (6,56).…”
mentioning
confidence: 99%